Hexa-band MIMO CPW Bow-tie Aperture Antenna Using Particle Swarm Optimization - A.K. hamid; W. Obaid (Institute of Advanced Engineering and Science, 2018)
A MIMO hexa-band Bowtie Antenna for Wi-Fi is proposed. The MIMO antenna can operate at six frequency bands: 2.4, 4.4, 6.1, 8.5, 10.25 and 12.8 GHz. The MIMO antenna consists of four loaded bowtie hexa-band antennas having the same structure. Each single antenna element is loaded with six metallic strips as well as interconnected parasitic rectangular components. The presented HFSS simulations will show that the MIMO loaded antenna can operate at six frequency bands including 2.4 GHz by obtaining the return loss results, radiation patterns, and other antenna parameters. It will be shown also that the MIMO bowtie antenna has a very low mutual coupling at all the operating frequencies for the specific loaded metallic strips width which was obtained using Particle Swarm Optimization technique.